Turismo de observação de cetáceos no Brasil - Gomes, Rosany Rossi Pereira (2021)
Whale-watching is a commercial, non-lethal activity to see, hear or swim with one of the dozens of species of cetaceans. This activity generates employment and income and can be an important opportunity for environmental awareness, but the lack of efficient management of whale-watching can cause negative impacts on these animals. Although there are scientific studies on the subject, there is still little data available on where and how whale-watching has been conducted in Brazil. In this sense, this study aims to investigate whale-watching in Brazil, based on a survey of their occurrence areas, target species and current norms and regulations. The methodology used in this research includes an extensive bibliographical review on areas of occurrence of cetaceans in Brazil, whale-watching, legal instruments and codes of conduct for the planning of this activity. Additionally, a search was carried out for reference areas for whale-watching on the homepages of agencies and tour operators. Data collection took place through telephone contact, e-mail and social networks of whale-watching agencies and tour operators. Three expeditions were also carried out to the Coastal Wildlife Reserve of Tibau do Sul (REFAUTS), Rio Grande do Norte, a reference area for dolphin-watching, to record the flow of tourist boats, in order to describe, in loco, how this activity has been conducted. At REFAUTS, a tourist boat boarding was carried out, in which the description of the tour for observing dolphins and the compliance of this tour with municipal law no 349/2007, which regulates shipping in this Reserve. In this study, seven cetacean species targeted by whale-watching were identified: humpback whale, Megaptera novaeangliae, southern right whale, Eubalaena australis, Guiana dolphin, Sotalia guianensis, spinner dolphin, Stenella longirostris, bottlenose dolphins, Tursiops truncatus, Amazon river dolphin, Inia geoffrensis, and tucuxi, Sotalia fluviatilis. In total, 29 reference areas for whale-watching are distributed in 11 Brazilian states, with 79% of these areas included in Protected Areas. From the analysis of compliance of the tour for observing dolphins in REFAUTS with municipal law no 349/2007, two infractions were registered: presence of two simultaneous boats in the restricted use area of this Reserve and boat engine connected at a distance less than 50 m of dolphins. The results presented in this study may support actions for monitoring and inspection of dolphin-watching, aiming to organize this activity and protect these animals. Thus, it is suggested that areas of occurrence of cetaceans in Brazil, still without legal protection, be protected through the creation of new Protected Areas. It is also suggested the promulgation of a legal instrument of national scope, which establishes guidelines for the planning of whale-watching in Brazil, focusing on the maximum number and speed of boats, duration and distance of the interaction between boats and cetaceans, licensing and training of boats conductors and a monitoring and inspection program for this activity